Stretchable wireless optoelectronic synergistic patches for effective wound healing - Qian Wang; Siyuan Cai; Guang Yao; Liyuan Zhang; Wenhao Lou; Youxin Chen; Qingqing Li; Maowen Xie; Xingyi Gan; Chenzheng Zhou; Taisong Pan; Min Gao; et al. (npj Flexible Electronics)
Abstract Physiotherapies play a crucial role in noninvasive tissue engineering for wound healing. However, challenges such as the implementation of complex interventions and unsatisfactory treatment outcomes impede widespread application. Here, we proposed a stretchable and wirelessly-powered optoelectronic synergistic patch with a dual-layer serpentine wireless receiver circuit to drive the optoelectronic modulation component. Optimized structure and impedance matching enable the patch to seamlessly attach to irregular skin surfaces and operate robustly over a 30% tensile strain range. Based on Sprague-Dawley rat wound model. The wound closure rate of the optoelectronic synergistic group significantly outperformed both monointervention and blank control groups. Mechanistically, optoelectronic synergistic intervention enhances the secretion of vascular endothelial marker proteins and growth factors, and stabilizes mitochondrial function during oxidative stress. Overall, the scalable amalgamation of flexible electronics, wireless transmission, and synergistic interventions promise to improve wound care.